Management of peritoneal dialysis under COVID-19: The experience in Sichuan Province People's Hospital, China. Issue 1 (January 2021) - Chen, Jin; Yin, Lijuan; Chen, Xiuling; Gao, Hui; Zhou, Qin; Li, Pengli; Liu, Wenshu; Ding, Hanlu; Hong, Daqing; Li, Guisen; Wang, Li
The outbreak of coronavirus disease 2019 (COVID-19) is becoming a severe challenge to China and the whole world. By now, there is no report about medical support to peritoneal dialysis (PD) patient during COVID-19 pandemic. In this essay, we summed up our safety measures on how to protect PD patients and our staffs, and our experience on how to ensure the dialysis treatment of PD patients during the pandemic period. Using of telehealth has potential to improve patient care quality. As a result, by applying all the actions and efforts above, most of patients got enough medical support. According to the patient survey, 11 patients (3.3% of the total) reduced their treatment of dialysis exchange due to the shortage of PD solution or the affection of the pandemic. None of the PD patient and staff reported COVID-19. We successfully prevented COVID-19 transmission and ensured medical safety in our PD patients during the crisis.